The Relationship between Efficiency and Share Prices: an Analysis of Chinese Bank State Ownership - Shi, Yao (2018)
This study analyses the efficiency, share prices and state ownership of Chinese listed banks from years 2007 to 2017. Stochastic Frontier Analysis is used to calculate cost efficiency and profit efficiency. System Generalised Method of Moments is used to do regression analysis on the three variables. It is found that Chinese banks have high cost and profit efficiency overall, but 2010 European debt crisis and 2016 deleveraging campaign have significant negative influences. State ownership has negative impact on share prices and efficiency. This confirms the Low Incentive Hypothesis proposed in this study. Profit efficiency is positively reflected in share prices, but cost efficiency is not significant. This confirms the Efficient Stock Market Hypothesis. Share prices have positive influence on cost efficiency, but have negative influence on profit efficiency. This confirms both the Low Capital Cost and Low Incentive Hypothesis.